A New Diterpene and Anti-inflammatory Sesquiterpene Lactones from Sigesbeckia orientalis - Engels, Nora S.; Gierlikowska, Barbara; Waltenberger, Birgit; Chang, Fang-Rong; Kiss, Anna K.; Stuppner, Hermann (Planta Medica, 2020)
Sigesbeckia orientalis, more commonly referred to as Herba Sigesbeckiae or Xi Xian Cao in traditional Chinese medicine and hy thiêm in traditional Vietnamese medicine, is used in China and Vietnam to treat inflammatory diseases such as arthritis, rheumatism, and joint pain. In initial investigations, the dichloromethane extract from the aerial parts of S. orientalis showed distinct inhibitory effects on the release of interleukin-8 in human neutrophils. Therefore, the purpose of the present study was the phytochemical investigation of the bioactive dichloromethane extract and the in vitro analysis of the effects of the isolated compounds on interleukin-8, interleukin-1β, tumor necrosis factor-α, and monocyte chemoattractant protein 1 release, and surface expression of adhesion molecules (CD11a, CD11b, and CD62L) in lipopolysaccharide-stimulated human neutrophils to identify the active principle(s). The separation of the bioactive dichloromethane extract using various chromatographic techniques led to the isolation of nine compounds. Their chemical structures were elucidated from nuclear magnetic resonance and mass spectrometry data. One diterpene, 17(13 → 14)-abeo-ent-3S*,13S*,16-trihydroxystrob-8(15)-ene, was identified as a new natural product. Three germacranolide sesquiterpene lactones inhibited interleukin-8 production with IC50 values between 1.6 and 6.3 µM, respectively, and tumor necrosis factor-α production with IC50 values between 0.9 and 3.3 µM, respectively. Furthermore, they significantly inhibited interleukin-1β and monocyte chemoattractant protein 1 production and diminished the effects of lipopolysaccharide on the surface expression of the adhesion molecules CD11a, CD11b, and CD62L. These findings support the traditional use of S. orientalis in the treatment of inflammatory diseases.
Keywords: Sigesbeckia orientalis; Asteraceae; inflammation; neutrophils; diterpenoids; sesquiterpene lactones